Implementation of Tourism Development Policy in North Minahasa Regency: A Case Study of Tunan Waterfall - Pangemanan, Heidiningsih; Mokat, Jetty E. H.; Wawointana, Thelma (International Journal of Information Technology and Education, 2025)
This study aims to analyze the implementation of tourism development policies in North Minahasa Regency, focusing on the Tunan Waterfall tourist site. The research is motivated by the suboptimal management of the region’s natural tourism potential, particularly at Tunan Waterfall, despite the issuance of Regional Regulation No. 4 of 2023 concerning the Master Plan for Tourism Development (RIPPARKAB) for 2023–2025. This study employs a qualitative approach with a descriptive method, using observation, interviews, and documentation as data collection techniques. The findings indicate that the implementation of tourism development policies still faces various challenges in terms of safety, comfort, attractiveness, accessibility, environmental sustainability, and contribution to local revenue (PAD). Determinant factors influencing implementation include policy communication, resource availability, implementers’ disposition, and bureaucratic structure (Edward III), as well as policy objectives, implementing agency characteristics, and socio-political conditions (Van Meter & Van Horn). Furthermore, a gap is identified between policy content and implementation context, as analysed using Grindle’s theory. The study recommends cross-sector synergy, institutional capacity building, and community participation to develop tourist destinations that are safe, comfortable, attractive, accessible, and sustainable.